The everyday life of global finance - Langley, Paul (Oxford University Press, 2008)
The Everyday Life of Global Finance explores the unprecedented relationships that now bind Anglo-American society with the financial markets. As mutual funds have increased in popularity and pension provision has been transformed, many more individuals and households have come to invest in stocks and shares. As consumer borrowing has risen dramatically and mortgage finance has embraced those deemed sub-prime, so the repayments of credit card holders and mortgagors have provided the basis for the issue and trading of bonds and other market instruments